Solid waste management and environmental education from the perspective of workers of a cooperative recycling | Gestão de resíduos sólidos e educação ambiental a partir da perspectiva dos trabalhadores de uma cooperativa de reciclagem - Ferreira, Maria das Graças Oliveira; Bilar, Alexsandro Bezerra Correia; Moura, Flávia Fernanda da Silva; Ferreira, Leonardo Rodrigues; Ribeiro, Eberson Pessoa (Revista Geama, 2016)
Before the exhaustion of natural resources, directly related to the disorderly growth of the cities, the lack of environmental awareness of its inhabitants and the mismanagement of solid waste produced, recycling is a process essential for sustainability. This research aimed to evaluate the perception of the community recycling cooperative in Jericó, in Triunfo/PE on the social, economic and environmental relevance of the activities they perform. To this end, questionnaires were applied with the social actors of this organization, as well as direct observation of the tasks carried out by them. While results, respondents stated that dealing with the recycling increased its interest on issues related to environmental education, as well as have come to understand the importance and consequences of the work they perform every day in the community where they live. The present study also revealed the contribution of cooperatives to promote recycling of local and sustainable development.